Regime-Switching, Stochastic Volatility, Fiscal Policy Shocks and Macroeconomic Fluctuations in Peru - Rodríguez, Gabriel; Santisteban, Joseph (Pontificia Universidad Católica del Perú. Departamento de Economía, 2024)
Following Chan and Eisenstat (2018a), we use a family of regime-switching models with time-varying parameters and stochastic volatility (RS-VAR-SV) to analyze the evolution of fiscal shocks impacts on Peru's economic growth from 1995Q1 to 2019Q4. Key findings include: (i) identification of two distinct economic regimes with different macroeconomic fundamentals tied to improvements in fiscal and monetary policy; (ii) enhanced model fi with the inclusion of stochastic volatility; (iii) a positive trend in the size of spending multipliers, though they remain below unity; (iv) during the 2008 Global Financial Crisis, capital expenditure shocks mitigated the decline in economic growth by 2 percentage points, highlighting their counter-cyclical potential. These findings are corroborated by robustness checks, which include changes in priors, variable reordering, adjustments in external and demand variables, and extending the sample to 2022Q4 to encompass the COVID-19 crisis.
Keywords: Regime-Switching Models; Fiscal Multipliers; Marginal Likelihood; Cross-Entropy; Bayesian Model Comparison; Peruvian Economy; Stochastic Volatility; https://purl.org/pe-repo/ocde/ford#5.02.01